Post‐Synthetic Ligand Exchange in Zirconium‐Based Metal–Organic Frameworks: Beware of The Defects!. (7th August 2018) - Taddei, Marco; Wakeham, Russell J.; Koutsianos, Athanasios; Andreoli, Enrico; Barron, Andrew R.
Abstract: Post‐synthetic ligand exchange in the prototypical zirconium‐based metal–organic framework (MOF) UiO‐66 was investigated by in situ solution 1 H NMR spectroscopy. Samples of UiO‐66 having different degrees of defectivity were exchanged using solutions of several terephthalic acid analogues in a range of conditions. Linker exchange only occurred in defect‐free UiO‐66, whereas monocarboxylates grafted at defect sites were found to be preferentially exchanged with respect to terephthalic acid over the whole range of conditions investigated. A 1:1 exchange ratio between the terephthalic acid analogue and modulator was observed, providing evidence that the defects had missing‐cluster nature. Ex situ characterisation of the MOF powders after exchange corroborated these findings and showed that the physical‐chemical properties of the MOF depend on whether the functionalisation occurs at defective sites or on the framework.